Isolation and antimicrobial activity of lactic acid bacteria from the traditional fermented food cangkuok semaung in Riau, Indonesia - Pratiwi, Nova Wahyu; Saryono, Saryono; Ismawati, Ismawati; Devi, Silvera; Suraya, Nabella; Lovenia, Nia; Nurafriza, Widya; Sasmita, Ellen Rosyelina; Ardhi, Aulia (Jurnal Ilmiah Pertanian, 2025)
Fermentation can be an effective step in addressing postharvest handling challenges and enhancing nutritional value through the conversion of perishable crops into more stable products. One of the traditional fermented foods originating from Kuantan Singingi Regency, Riau Province, Indonesia, is cangkuok semaung (CS). This food is prepared by fermenting all fruit components of the semaung (Pangium edule). This research aimed to isolate and identify lactic acid bacteria (LAB) from CS and investigate their antimicrobial properties. The bacteria were isolated from the food, purified using the quadrant streak method on the De Man–Rogosa–Sharpe agar, and continued with morphological analysis and antimicrobial activities evaluation. The findings of this study revealed that 45 isolates were gram-positive bacteria identified as Lactobacillus sp. Among the LAB isolates, the highest antimicrobial activity against Escherichia coli, Staphylococcus aureus, Acinetobacter baumannii, and Klebsiella pneumoniae were shown by isolates of S12, S14, S27, and S24, respectively. These results suggest that LAB from CS, especially isolates S12 and S14, have promising antimicrobial properties and show potential as probiotic candidates that merit further investigation into possible applications in food and health sectors.